Improving Mathematics Learning Outcomes Through Baamboozle Media with the Numbered Heads Together Model in Elementary School - Suastika, I Ketut; Nafi'ah, Muti'atun; Ambarwati, Adna Arum (Educare : Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
This study aims to improve the learning outcomes of mathematics students in grade IV of SDN Tanjungrejo 2 Malang through the application of Baamboozle interactive media combined with the Numbered Heads Together (NHT) learning model. The background of this research is based on the low mathematics learning outcomes, as shown by the average student score of 66.07 which is still below the Minimum Completeness Criteria (KKM) which is 75. This study uses the Kemmis and McTaggart model Class Action Research (PTK) method which is carried out in two cycles, each consisting of planning, implementation, observation, and reflection stages. The learning outcome data was obtained through an evaluation test at the end of each cycle and was analyzed in a quantitative descriptive manner by calculating the average score and percentage of learning completeness. The results showed that the average student score increased from 66.07 in the pre-cycle to 73.57 with 60.71% learning completeness in the first cycle, and increased again to 80.35 with 85.71% learning completeness in the second cycle. This finding proves that the application of Baamboozle interactive media combined with the Numbered Heads Together model is effective in improving the mathematics learning outcomes of grade IV students of SDN Tanjungrejo 2 Malang. The implications of this study show that the integration of interactive digital media with cooperative learning models can be an alternative to innovative, effective, and fun learning strategies in elementary schools.